Pengaruh Mozaik terhadap Motorik Halus Anak - Rambe, Achnes Oktavia; Sitorus, Ahmad Syukri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The motivation behind this examination is to learn the way in which mosaic influences youngsters' fine coordinated movements. This audit was coordinated with to class, to be explicit the exploratory class and the contol class. The hard and fast number of 40 children at Ummi Erni Kindergarten, inexperimental class there were 20 young people and in control class as many as 20 children. Utilizing a kind of nonquivalent control bunch plan and semi tries, this strategy for research is done. Data assessment in this study went through a couple of stages, explicitly normality,homogeneity and hypothesis. The typical information breezed through the ordinariness assessment, and the ordinary sig esteem was more noteworthy than 0,05, demonstrating that the information from each class were regularly dispersed. The homogeneity test yielded a sig esteem more noteworthy than 0,05, showing that the information from the two classes were indistinguishable. Speculation testing with a free example test yielded Tcount > Ttable (2,101), after which Ha was acknowledged and Ho was dismissed with sig 0,00 0,05. The information were critical, and there was a distinction of 508 or 5,08 percent between the exploratory and control classes. This concentrate subsequently shows that mosaic method essentially affects youngsters' fine coordinated movements. Keywords: Mosaic, Fine Coordinated movements, Youngsters